UJI FORMALIN PADA IKAN ASIN GURAMI DI PASAR TRADISIONAL PEKANBARU - Nadya Yulisa Yulisa; Enikarmila Asni; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Formalin is aqueous solution of chemical compund formaldehyde (30-50%) and methyl alcohol (10-20%). Missapropriation of formalin as perservatives has became society common issue, which was the use of formalin on foods, such as salted carps. This study aimed to determine the formaldehyde substance in salted carps that sold in traditional markets. This is a descriptive laboratory study where 6 traditional markets administered by the Office of Pekanbaru City Market have obtained as samples. Tests were conducted in the Laboratory of Biochemistry Faculty of Medicine, University of Riau. Qualitative study was to see whether or not salted carps contained any formaldehyde substances and semi-quantitative study was to determine the formaldehyde concentrate in salted carps. Examination of 20 salted carps as samples showed a qualitative result that all samples positively contained formaldehyde, which was indicated by the purple color in the formalin test. Result of semi- quantitative test showed a diversity of formaldehyde concentration in the range 1.89 % - 7.66%, which was leading to a conclusion samples wether population were positively contained formaldehyde.Key word: formaldehyde, salted carp, traditional market